Classification of Male Athletes Based on Critical Power - Olaya-Cuartero, Javier; Pueo, Basilio; Penichet-Tomas, Alfonso; Jimenez-Olmedo, Jose M. (International Journal of Sports Medicine, 2024)
This study aimed to classify male athletes based on their performance levels derived from running critical power (CP) using the 9/3-minute Stryd CP test, enabling customized training strategies and goal setting. Twenty-four trained athletes underwent the 9/3-minute running CP test on a certified 400-m athletics track. Hierarchical cluster analysis using Ward's method categorized athletes based on CP into distinct performance tiers. Three clusters were identified with centroids of 3.87±0.12, 4.45±0.17, and 5.14±0.29 W/kg. Five performance tiers were defined through ordinary least square linear regression based on power (W/kg): Tier 1: Fair (2.9 to 3.6 W/kg), Tier 2: Tourist (3.6 to 4.2 W/kg), Tier 3: Regional (4.2 to 4.8 W/kg), Tier 4: National (4.8 to 5.5 W/kg), Tier 5: International (5.5 to 6.1 W/kg). Low semi-partial R-squared (SpR2) values (0.02 to 0.05) indicated minimal homogeneity loss when merging clusters. R-squared (R2) explained 89% to 96% of CP variance, emphasizing cluster analysis effectiveness. The linear regression model demonstrated a strong fit (r2+=+0.997) with a significant intercept (3.22 W/kg), slope (0.63 W/kg/tier), and a low standard error of estimate (0.045 W/kg). This classification offers insights into male athlete performance levels based on CP, facilitating targeted training programs for varying performance levels.
Keywords: performance; clustering; linear regression; running; tiers; training